Depolymerization of Poly(ethylene terephthalate) Wastes through Glycolysis using Lewis Acidic Bentonite Catalysts - Jeya, Gopal; Anbarasu, Murugan; Dhanalakshmi, Ravikumar; Vinitha, Viswanathan; Sivamurugan*, Vajiravelu (Asian Journal of Chemistry, 2019)
In the present investigation, the authors explored the depolymerization of waste poly(ethylene terephthalate) (PET) beverage bottles using glycolysis (transesterification) catalyzed by Al3+, Fe3+ and Zn2+ impregnated bentonite catalysts. Heterogeneous catalysts such as clay, zeolite, alumina etc. preferred over homogeneous catalysts, thus we focused on the development of solid acid catalysts based on economically viable clay catalysts. The desired Lewis acidic nature was introduced by wet impregnation method at variable metal ion to clay ratio such as 0.5, 1.0, 2.0, 3.0, 4.0 and 5.0 wt. %. The effect of metal-ion loading on the surface area, pore volume and crystalline nature of the bentonite has been evaluated by nitrogen adsorption and desorption studies and XRD. The PET wastes collected from post-consumer beverage bottles were depolymerized using ethylene glycol as a glycolyting agent afforded bis(2-hydroxy ethyl)terephthalate (BHET) in 85-90 % yield under optimized conditions. The yield of BHET was observed to be increasing with increase in Lewis acidic metal ions loading from 0.5 to 4.0 wt. % as well as increase in catalysts to PET ratio. Among the catalysts, Al3+ and Zn2+-bentonite catalysts showed higher yield of BHET up to 90 % at 4 and 5 wt. % loading of metal-ion.